Japanese patterns of behavior - Lebra, Takie Sugiyama (University of Hawaii Press, 1976)
This book still provides the fundamentals needed to understand the Japanese mind, following the ethnographic tradition, is commit-ted to drawing a boundary of Japanese culture under the assump-tion that no other culture shares completely the same boundary.